Clinical evaluation of static scapular posture in overhead athletes with asymptomatic shoulder injuries - Papandreou, M.; Diamantis, E.; Vrachlioti, V.-I.; Billis, E.; Gliatis, J. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Several etiologic factors have been postulated in overhead athletes according to their shoulder injuries, such as the scapular posture asymmetries. The measurement of the acromion border distance has been considered as reliable clinical test for evaluating the static scapula posture. The aim of this study was to quantify the differences in scapular posture between the dominant and non-dominant shoulders in two static positions in volleyball and swimmers athletes with asymptomatic shoulder injuries using the sliding calliper device. METHODS: Twenty athletes involved in volleyball and swimming sports were recruited. Their mean age was 25.4±8.09 years and BMI 22.68±1.63 kg/cm2. All athletes had asymptomatic traumatic shoulder injuries. Two clinical tests were used to estimate scapula posture between the two groups of athletes using a sliding calliper device. In the first method the distance between the posterior border of the acromion in supine position and the table (AT) was measured, and in the second one the distance between the posterior border of the acromion and the wall (AW) was measured in standing. RESULTS: Statistical significant differences found in AW position in the volleyball compared with swimmer athletes (F=8.883, S=0.008, P<0.05). The difference in scapula posture in AW position was higher (14.90±4.99 mm) in the volleyball than in swimmers athletes (8.34±4.84). CONCLUSIONS: These findings could have implications using the assessment of acromion border as an outcome measure of the scapula asymmetry posture in overhead athletes with asymptomatic shoulder injuries. Due to the limited sample size, this study should be considered as pilot